Conceptualizing 'everyday resistance' : a transdisciplinary approach - Johansson, Anna; Vinthagen, Stellan (New York, NY : Routledge, 2020)
"Everyday resistance is about the many ways people undermine power and domination through their routine and everyday actions. Unlike open rebellions or demonstrations, it is typically hidden, not politically articulated, and often ingenious. But because of its disguised nature, it is often poorly understood as a form of politics and its potential underestimated. Conceptualizing Everyday Resistance presents an analytical framework and theoretical tools to understand the entanglements of everyday power and resistance. These are applied to diverse empirical cases including queer relationships in the context of heteronormativity, Palestinian daily life under military occupation, workplace behaviors under office surveillance, and the tactics of fat acceptance bloggers facing the War against obesity. Johansson and Vinthagen argue that everyday resistance is best understood by accounting for different repertoires of tactics, relations between actors, and struggles around constructions of time and space. Through a critical dialogue with the work of James C. Scott, Michel de Certeau, and Asef Bayat, they aim to reconstruct the field of resistance studies, expanding what counts as resistance and building systematic analysis. Conceptualizing Everyday Resistance offers researchers and students from different theoretical and empirical backgrounds, an essential overview of the field and a creative framework that illuminates the potential of all people to transform society"--
OCLC-licensed vendor bibliographic record.
Keywords: Government, Resistance to; Resistance (Philosophy) -- Political aspects; Social change; POLITICAL SCIENCE / General; SOCIAL SCIENCE / General; POLITICAL SCIENCE / History & Theory